Disaccharide-Mediated Regulation of Sucrose:Fructan-6-Fructosyltransferase, a Key Enzyme of Fructan Synthesis in Barley Leaves - Müller, Joachim (American Society of Plant Physiologists, 2000)
Previous work has indicated that sugar sensing may be important in the regulation of fructan biosynthesis in grasses. We used primary leaves of barley (Hordeum vulgare cv Baraka) to study the mechanisms involved. Excised leaf blades were supplied in the dark with various carbohydrates. Fructan pool sizes and two key enzymes of fructan biosynthesis, sucrose (Suc):Suc-1-fructosyltransferase (1-SST; EC 2.4.1.99) and Suc:fructan-6-fructosyltransferase (6-SFT; EC 2.4.1.10) were analyzed. Upon supply of Suc, fructan pool sizes increased markedly. Within 24 h, 1-SST activity was stimulated by a factor of three and 6-SFT-activity by a factor of more than 20, compared with control leaves supplemented with mannitol (Mit). At the same time, the level of mRNA encoding 6-SFT increased conspicuously. These effects were increased in the presence of the invertase inhibitor 2,5-dideoxy-2,5-imino-d-mannitol. Compared with equimolar solutions of Suc, glucose (Glu) and fructose stimulated 6-SFT activity to a lesser extent. Remarkably, trehalose (Tre; Glc-α-1 and 1-α-Glc) had stimulatory effects on 6-SFT activity and, to a somewhat lesser extent, on 6-SFT mRNA, even in the presence of validoxylamine A, a potent trehalase inhibitor. Tre by itself, however, in the presence or absence of validoxylamine A, did not stimulate fructan accumulation. Monosaccharides phosphorylated by hexokinase but not or weakly metabolized, such as mannose (Man) or 2-deoxy-Glc, had no stimulatory effects on fructan synthesis. When fructose or Man were supplied together with Tre, fructan and starch biosynthesis were strongly stimulated. Concomitantly, phospho-Man isomerase (EC 5.3.1.8) activity was detected. These results indicate that the regulation of fructan synthesis in barley leaves occurs independently of hexokinase and is probably based on the sensing of Suc, and also that the structurally related disaccharide Tre can replace Suc as a regulatory compound.